Catalytic effect of Ti on dehydrogenation of Na3AlH6: A first principles investigation. (21st September 2015) - Yu, H.Z.; Dai, J.H.; Song, Y.
Abstract: In the present work, ab initio calculations were performed for the Ti-doped Na3 AlH6 to investigate influence of dopant Ti on the hydrogenation/dehydrogenation properties of Na3 AlH6 . Substitution of Ti for Al and Na atoms, respectively, and an interstitial occupation of Ti in this compound were studied. It was found that Ti prefers to substitute for Al atom with the lowest occupation energy of 0.64 eV among the considered systems. The influence of Ti on hydrogenation/dehydrogenation properties of Na3 AlH6 was sensitive to its occupation behavior. Ti greatly decreases the dehydrogenation energy of Na3 AlH6 if it substituted for a Na atom. A mechanism described the Ti catalytic reversible reaction of NaAlH4  → Na3 AlH6 was proposed based on the electronic analysis in this paper. Graphical abstract: Highlights: A transport media of Al–H complex was observed in Ti doped Na3 AlH6 . Dopant Ti stretches Al–H bond and promotes the hydrogen dissociation from Na3 AlH6 . A mechanism that Ti improves dehydrogenation properties of Na3 AlH6 was proposed.